Michael Collins [videorecording (DVD)] - Jordan, Neil, 1950-; Neeson, Liam; Quinn, Aidan; Rea, Stephen; Rickman, Alan; Roberts, Julia, 1967-; Hart, Ian, 1964-; Dance, Charles; Menges, Chris, 1940-; Goldenthal, Elliot (Archive collection., 2015)
Michael Collins plays a crucial role in the establishment of the Irish Free State in the 1920s, but becomes vilified by those hoping to create a completely independent Irish republic.